Fibroblast growth factor receptor (FGFR) inhibitors in cholangiocarcinoma: current status, insight on resistance mechanisms and toxicity management. (2nd January 2022) - Chakrabarti, Sakti; Finnes, Heidi D.; Mahipal, Amit
ABSTRACT: Introduction: Cholangiocarcinoma (CCA) frequently presents with an advanced disease precluding curative surgery and shows modest response to chemotherapy. Advancements in genomic profiling have unfolded critical pathophysiologic underpinnings of CCA, leading to the development of targeted therapies with encouraging early results. Of the targetable genomic alterations, fibroblast growth factor receptor-2 ( FGFR-2 ) fusions or rearrangements are present in 10–15% of patients with intrahepatic CCA. Clinical trials demonstrating significant antitumor activity of FGFR inhibitors in FGFR-2 fusion or rearrangement enriched chemotherapy-refractory patients led to FDA approval of FGFR inhibitors, pemigatinib and infigratinib, in the second-line setting. We identified peer-reviewed articles on FGFR inhibitors utilizing the PubMed database published between 2015 and 2021. Areas covered: This article provides an overview of clinical and biological characteristics of FGFR-driven CCA, pharmacology and antitumor activity of currently available FGFR inhibitors, and the evolving knowledge of drug resistance mechanisms. Additionally, toxicities associated with FGFR inhibitor use and their management have been described. Expert opinion: The development of FGFR inhibitors is a significant advancement in the therapeutic paradigm of advanced CCA. Ongoing research utilizing FGFR inhibitors in treatment-naïve patients, elucidation of resistance mechanisms to harness future trials, and exploration of combination strategies will transform the treatment landscape of CCA.